Rapid and visual detection of SARS-CoV-2 by reverse transcriptase - loop mediated isothermal amplification(RT-lamp). - Neupane, Anant (2021)
ABSTRACT: Background: Coronavirus disease 2019(COVID-19) caused by SARS-CoV-2, is a global pandemic identified in December in China. Majority of the world around the globe was affected by COVID-19 creating a panic situation all round the world. Proper use of personal protective equipment and care identification were the most successful approaches for controlling the disease to spread RT-PCR is the only gold standard molecular approach for the diagnosis of viral genetic material which is costly, requires trained manpower and result output time is relatively long. Hence in our country like Nepal other molecular techniques like RT-LAMP may be alternatively used to diagnose the SARS-CoV-2 which is relatively cost effective, and rapid. This study aims to study the rapid and visual method for detection of SARS-CoV-2 by reverse transcriptase loop mediated isothermal amplification. Objective: To identify the SARS-CoV-2 rapid visual RT-LAMP. Method: This study was conducted in DECODE genomics, Baghbazar, Kathmandu, Nepal. Patient requested for COVID-19 test with all age groups were included in the study. Study duration was of 6 months. Ethical approval was taken from the Institutional Review Board of Institute of Medicine. Informed consent was taken from each patients. A total of 100 samples were randomly selected. Nasopharyngeal/ Oropharyngeal swab were collected and transported in viral transport medium. RNA from the sample were extracted and COVID-19 test was performed by using RT_LAMP assay and the result were compared with the gold standard method RT-PCR. Results: Out of 100 patients 40 patients were diagnosed positive by the RT-PCR while 39 were diagnose as positive by RT-LAMP with 1 case identified as false positive and 2 cases were identified as false negative. The overall sensitivity and specificity of RT-LAMP when compared with that of RT-PCR was found to be 95% and 98.3%. Conclusion:The results that the use of RT-LAMP method can be used as an alternative molecular diagnosis of COVID-19. In the context of developing country like Nepal RT-LAMP technique would be the alternative means fort the detection of SARS-CoV-2 which is cost effective, sensitive, specific, less time consuming, does not requires trained manpower, and conveniently carried out without sophisticated instruments. Key Words: Coronavirus disease 2019, Reverse Transcriptase loop mediated isothermal amplification, Reverse transcriptase polymerase chain reaction.